'Well, if the kids can do it, I can do it': older rehabilitation patients' experiences of telerehabilitation. (18th February 2016) - Shulver, Wendy; Killington, Maggie; Morris, Claire; Crotty, Maria
Abstract: Background and objective: Although trials continue to emerge supporting the role of telerehabilitation, implementation has been slow. Key users include older people living with disabilities who are frequent users of hospital rehabilitation services but whose voices are rarely heard. It is unclear whether the use of technologies and reduced face‐to‐face contact is acceptable to these people. We report on a qualitative study of community dwelling participants who had received a home telerehabilitation programme as an alternative to conventional rehabilitation. Design: Thirteen older participants, three spouses and one carer were interviewed. All had participated in an individualized therapy programme, using a combination of face‐to‐face and video consults with therapists. The programme used 'off‐the‐shelf' technologies including iPads for videoconferencing and electronic FitBit R devices. Interviews were recorded, transcribed verbatim and analysed using NVivo software. Results: Thematic analysis resulted in five emergent themes: (i) telerehabilitation is convenient; (ii) telerehabilitation promotes motivation and self‐awareness; (iii) telerehabilitation fosters positive therapeutic relationships; (iv) mastering technologies used by younger relatives is a valued aspect of telerehabilitation; and (v) Telerehabilitation does not replace traditional face‐to‐face rehabilitation therapies. Conclusions: Participants found telerehabilitation convenient and motivating, coped well with the technology and developed positive therapeutic relationships. The learning and practice aspects sat well in the context of a rehabilitation programme. The use of commercially available technologies may have contributed to respondents' high levels of acceptability. The perception of telerehabilitation as complementary to in‐person care and the expectation of technological support have implications for the implementation and delivery of telerehabilitation services to older people.